Biodiesel resource for sustainable microgrid system: a spotlight on the state-of-the-art, application, challenges and enabling policy - Daniel Akinyele; Olakunle Olabode; Funso Ariyo; Adeonipekun Adeshina (Discover Sustainability)
Abstract This paper presents the state-of-the-art and the problems affecting the progress of biodiesel (bioD) fuel, storage, and the enabling policy. The work examines the application of bioD in microgrids (µ-grids) and the impact of using different bioD blends coupled with other resources such as solar and biogas (bioG). The paper considers PV, bioG and bioD-based µ-grid simulation for standalone applications. A µ-power optimization tool is employed to determine the sizes of PV, battery, inverter, bioD generator (bioDG) and the bioG systems to supply a demand of 32,685.75 kWh/yr for 15 houses in Nigeria. Three µ-grids – PV-only, PV/bioDG and the PV/BioG/bioDG systems are compared using the energy generated, unmet load (uL), cost and the emissions saved by different blends. The PV-only delivers 43,496 kWh/yr of electricity with uL of 2,479 kWh/yr (7.59%), capacity shortage of 3,294 kWh/yr (10.1 %), and excess electricity of 7,244 kWh/yr (16.7 %). In the second case, an 11 kW bioDG is integrated with the PV; the PV and the bioDG generate 43,467 and 12,599 kWh/yr of electricity, respectively, with uL of 0%. The PV/BioG/bioD µ-grid produced a total energy of 37,453 kWh/yr, which completely satisfies the users’ demand. The hybrid configurations also achieve appreciable emissions saving compared to a PV/diesel option. The emissions saved by the hybrid systems for different blends—B100 to B5 range from 9,120 to 456 kg/yr. These results demonstrate a direct proportionality of emissions to the bioD in the blends. The PV/BioG/bioDG µ-grid can provide eco-friendly and reliable supply. A conceptual policy framework is also introduced in the paper, which provides insights into social acceptance of the bioD fuel for local electrification planning and development..